Obesity and hypoalbuminaemia are independent risk factors for readmission and reoperation following primary total knee arthroplasty. (June 2020) - Sloan, Matthew; Sheth, Neil P.; Nelson, Charles L.
Abstract : Aims: Rates of readmission and reoperation following primary total knee arthroplasty (TKA) are under scrutiny due to new payment models, which penalize these negative outcomes. Some risk factors are more modifiable than others, and some conditions considered modifiable such as obesity may not be as modifiable in the setting of advanced arthritis as many propose. We sought to determine whether controlling for hypoalbuminaemia would mitigate the effect that prior authors had identified in patients with obesity. Methods: We reviewed the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database for the period of January 2008 to December 2016 to evaluate the rates of reoperation and readmission within 30 days following primary TKA. Multivariate logistic regression modelling controlled for preoperative albumin, age, sex, and comorbidity status. Results: Readmission rates only differed significantly between patients with Normal Weight and Obesity Class II, with a decreased rate of readmission in this group (odds ratio (OR) 0.82; 95% confidence interval (CI) 0.71 to 0.96; p = 0.010). The only group demonstrating association with increased risk of reoperation within 30 days was the Obesity Class III group (OR 1.38; 95% CI 1.05 to 1.82; p = 0.022). Hypoalbuminaemia (preoperative albumin < 35 g/L) was significantly associated with readmission (OR 1.62; 95% CI 1.41 to 1.86; p < 0.001) and reoperation (OR 1.52; 95% CI 1.18 to 1.96; p = 0.001) within 30 days. Conclusion: In this study, hypoalbuminaemia appears to be a more significant risk factor for readmission and reoperation than even the highest obesity categories. Future studies may assess whether preoperative albumin restoration or weight loss may improve outcomes for patients with hypoalbuminaemia. The implications of this study may allow surgeons to discuss risk of surgery with obese patients planning to undergo primary TKA procedures if other comorbidities are adequately controlled. Cite this article: Bone Joint J 2020;102-B(6 Supple A):31–35.